Phenotypic Expression of Autoimmunity in Children With Autoimmune Thyroid Disorders - Aversa, Tommaso; Corica, Domenico; Zirilli, Giuseppina; Pajno, Giovanni Battista; Salzano, Giuseppina; De Luca, Filippo; Wasniewska, Malgorzata (Frontiers in Endocrinology, 2019)
Autoimmune thyroid diseases (AITDs), including Hashimoto’s thyroiditis (HT) and Graves’ disease (GD), tend to aggregate with other non-thyroidal autoimmune diseases (NTADs). Aim of this Mini-review is to report the most recent insights concerning the clustering of NTADs in pediatric patients with either HT or GD, the pathophysiology of AITDs and the metamorphic thyroid autoimmunity. A systematic literature research of the last fifteen years, according to EQUATOR statement, was carried out through MEDLINE via PubMed (http://www.ncbi.nlm.nih.gov/pubmed/) Embase, CINAHL, Cochrane Library, based on the following keywords: (autoimmune thyroid disease OR Hashimoto thyroiditis OR Grave’s disease) AND (autoimmune comorbidities OR extra-thyroidal autoimmune disorders) AND (children OR adolescents OR pediatrics) AND (celiac disease OR type 1 diabetes mellitus OR arthropathies OR cutaneous diseases) AND (Turner syndrome OR Down syndrome). One-hundred and twenty-eight manuscripts were extrapolated but only seventeen were eligible. On the basis of the available reports it may be inferred that clustering of NTADs can be significantly modified by both patients’ age at AITDs presentation and association with Down’s syndrome (DS). Particularly, the association of AITDs with celiac disease and type 1 diabetes was most commonly reported in children than in adults. A sequential shifting from HT to GD has been described in children with AITDs, and it seems to be more frequent in children with DS than in those without DS. Coexistence of autoimmune diseases might be the result of a complex interaction among genetics, environment and epigenetic modifications that are able to affect gene expression, immune system response and, finally, the pathogenesis of autoimmune diseases.